A high density linkage map and quantitative trait loci for tree growth for New Zealand mānuka (Leptospermum scoparium). Issue 4 (2nd October 2019) - Chagné, David; Ryan, Julie; Saeed, Munazza; Van Stijn, Tracey; Brauning, Rudiger; Clarke, Shannon; Jacobs, Jeanne; Wilcox, Philip; Boursault, Emma; Jaksons, Peter; Jones, Dan; Thrimawithana, Amali; et al.
ABSTRACT: A high-density linkage map was constructed for mānuka ( Leptospermum scoparium ) genotyping by sequencing (GBS) and a segregating population developed using accessions from the East Cape region of New Zealand. Parental maps were constructed using 1140 and 1509 SNPs markers grouped into 11 linkage groups for both parents spanning a total of 1242.8 and 1616.2 cM, respectively. Quantitative trait loci (QTL) analysis was performed for tree height. In total, 10 QTLs were detected after the measured variable was adjusted for the block effect in the field. The significant QTLs were inherited from both parents (five each) and were located on LG2, 3, 6, 7, 9 and 10. This is the first high-density linkage map constructed using thousands of genetic markers obtained by GBS, the first QTL reported for a New Zealand native tree species, which represents a model for future genetic analysis of indigenous New Zealand species.